Utility of state-level influenza disease burden and severity estimates to investigate an apparent increase in reported severe cases of influenza A(H1N1) pdm09 – Arizona, 2015–2016. Issue 11 (14th June 2018) - Russell, K.; Herrick, K.; Venkat, H.; Brady, S.; Komatsu, K.; Goodin, K.; Berisha, V.; Sunenshine, R.; Perez-Velez, C.; Elliott, S.; Olsen, S. J.; Reed, C.
Abstract: The Arizona Department of Health Services identified unusually high levels of influenza activity and severe complications during the 2015–2016 influenza season leading to concerns about potential increased disease severity compared with prior seasons. We estimated state-level burden and severity to compare across three seasons using multiple data sources for community-level illness, hospitalisation and death. Severity ratios were calculated as the number of hospitalisations or deaths per community case. Community influenza-like illness rates, hospitalisation rates and mortality rates in 2015–2016 were higher than the previous two seasons. However, ratios of severe disease to community illness were similar. Arizona experienced overall increased disease burden in 2015–2016, but not increased severity compared with prior seasons. Timely estimates of state-specific burden and severity are potentially feasible and may provide important information during seemingly unusual influenza seasons or pandemic situations.